Assessing Financial Performance in Consumer Goods Manufacturing: The Role of Debt to Assets Ratio, Current Ratio, and Inventory Turnover - Desshyfa, Rizana Tarissa; Purwanto, Edi (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2024)
Manufacturing companies in the consumer goods sector play a vital role in satisfying market demands and attracting investors, especially those listed on the Indonesia Stock Exchange (IDX). This study assesses the financial performance of consumer goods manufacturing companies listed on the IDX, focusing on the cosmetics and household goods sub-sector. It examines the influence of Debt to Assets Ratio (DAR), Current Ratio (CR), and Inventory Turnover on financial performance. Data analysis utilizes panel data regression tests. Findings reveal that all three variables significantly impact financial performance, suggesting that managing these ratios can enhance company profitability and value. The study offers practical recommendations for improving asset management, liquidity, and inventory turnover to optimize consumer goods manufacturing sector financial performance.